Предмет: Алгебра,
автор: сериаломан1
Помогите, срочно нужно.
Приложения:
Ответы
Автор ответа:
0
a) -6x+3x^2+3x^2-6x+x-2= -11x+6x^2-2
б) 3(4x^2-4x+1)+12x= 12x^2-12x+3+12x= 12x^2+3
в) x^2+6x+9-x^2+2x-2x-4=6x+5
Ну вроде бы так.
б) 3(4x^2-4x+1)+12x= 12x^2-12x+3+12x= 12x^2+3
в) x^2+6x+9-x^2+2x-2x-4=6x+5
Ну вроде бы так.
Похожие вопросы
Предмет: Математика,
автор: meninormkat
Предмет: Алгебра,
автор: SalatTorchun
Предмет: История,
автор: iiiiiiioio
Предмет: История,
автор: aigerimapvl
Предмет: Экономика,
автор: fansm1